Difficult-to-treat psoriatic arthritis. Data from the All-Russian registry of patients with psoriatic arthritis - E. Yu. Loginova; T. V. Korotaeva; E. E. Gubar; Yu. L. Korsakova; E. L. Nasonov (Современная ревматология)
Objective: to characterize patients with difficult-to-treat (D2T) psoriatic arthritis (PsA) and to assess risk factors for its development.Material and methods. The study included 263 PsA patients treated with biologic disease- modifying antirheumatic drugs (bDMARDs) or targeted synthetic DMARDs (tsDMARDs) and followed up for ≥2 years in the All-Russian Registry of PsA Patients. All patients underwent a standard clinical and laboratory examination, and concomitant diseases were recorded. PsA activity was assessed using DAPSA index and minimal disease activity criteria.Results and discussion. 152 (57.8%) patients who received 1 bDMARD/tsDMARD for 2 years achieved remission/low disease activity (LDA) according to DAPSA and were categorized as having non-D2T PsA. Other 111 (42.2%) patients switched ≥2 bDMARDs/tsDMARDs within 2 years, 71 (27%) of them achieved remission/LDS, and 40 (15.2%) patients who continued to have high or moderate PsA activity met the D2T criteria. A comparative analysis of 40 patients (20 men and 20 women) with D2T PsA and 152 patients (78 men and 74 women) with PsA who did not fulfil the D2T criteria was performed. It was found that patients with D2T PsA had a significantly longer duration of PsA (p=0.017), more frequent polyarthritis (p=0.014), dactylitis (p=0.004), enthesitis (p=0.001), BSA >10% (p=0.008), onycholysis (p=0.001), HAQ >0.5 (p=0.039), depression (p=0.007) and elevated blood uric acid levels (p=0.023).Conclusion. In real-life clinical practice, the D2T variant of PsA is reported in 15% of cases. Treatment-resistant PsA patients are characterized by a longer duration of PsA, more widespread severe psoriasis with onycholysis and are more likely to have polyarthritis, dactylitis, enthesitis and functional disorders at the time of bDMARD prescription, as well as concomitant diseases, especially depression and hyperuricaemia.